STRATEGI PENINGKATKAN PENDIDIKAN KARAKTER ANAK DENGAN MEMANFAATKAN TEKNOLOGI DI DESA BOGOR BARU - Alka Kianda; Deri Wanto; Hendra Harrmi (ILJ: Islamic Learning Journal, 2023)
: This research aims to identify effective strategies for enhancing children's character education through the utilization of technology in Desa Bogor Baru. The research employs qualitative analysis method and utilizes primary and secondary data through observation, interviews, and documentation. The proposed strategies include the development of character education applications and software, online learning platforms, collaboration with communities and organizations, training for educators and parents, as well as the utilization of digital media. Through the implementation of these strategies, it is expected to improve children's character education by harnessing the potential of technology. The findings of this research are anticipated to provide insights and recommendations for the government, educational institutions, and communities in their efforts to enhance children's character education in Desa Bogor Baru.